PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS CHEMO- EDUTAINMENT (CET) - Hulandari, Febri; Rahmi, Elvy (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Abstract This research is motivated by the facts found in the field that the teaching materials used at SMAN 2 Rambatan have not been able to attract students' interest in learning, so that students have difficulty understanding the material and solving problems related to the material. The purpose of this research is to produce a Chemo-Edutainment (CET)-based Student Worksheet on colloidal system material that is valid and practical. The type of research that I use is development research using a 4-D development model consisting of 4 stages, namely define, design, develop, and disseminate. The CET-based LKPD product was validated by two chemistry education lecturers and one chemistry teacher using a validation sheet. Practicality trials were carried out by 14 students of class XI MIPA SMAN 2 Rambatan using a response questionnaire. The results obtained are LKPD based on CET which has characteristics consisting of components including LKPD title, student identity, instructions for use, competencies to be achieved, chemistry info, simple experiments and practice questions in the form of educational games that attract interest. students to do the exercises, the last component is the existence of a golsarium and bibliography. The validity obtained by this CET-based LKPD obtained a percentage of 94.35% with very valid criteria. The practical results of this CET-based LKPD obtained a percentage of 93.80% with very practical criteria. With this, it can be concluded that the CET-based worksheets designed are valid and practical to be used as teaching materials in the learning process. Keywords: LKPD, Chemo-Edutaintment, Validity, Practicality